Pendampingan Pengembangan Papan Buletin untuk Guru SD Kecamatan Sukamakmur, Bogor, Jawa Barat - Kunto Imbar Nursetyo; Erry Utomo; Muhammad Azhar Thifal; Ersa Mauliza (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Based on data from SDN Sukamakmur 1, SDN Sukamakmur 2 and SDN Sukamakmur 3 students, the average grade of subjects in the odd-semester tests for the 2017/2018 school year is 5.5, while the minimum Mastery Criteria, or KKM in the three schools is 6.5. The low learning outcomes of the students, based on the analysis made by choosing the methods and media used by the teacher, are less interesting and less accurate, making the lesson deliveries too difficult to remember. The results of the observations on the three above-mentioned SDNs indicate that teachers are still adopting the traditional approach. The sign is that the teacher still plays the dominant role in activities while the students are only listeners and information recipients. During the learning processes, students only listen to the teacher's explanation and record or summarize the important things from the material provided by the teacher. Therefore, it is necessary to strive for the use of media and the selection of a suitable approach in the learning process as well as an interesting atmosphere, so that the students learn more actively and ultimately the student activities and learning outcomes increase. The approach offered for the implementation of the civilian service program is an assistance model with the following steps: 1) preparation; 2) evaluation; 3) alternative planning of programs or activities; 4) formulation of the action plan; 5) status of implementation (implementation) of the program or activity; 6) evaluation; and 7) Termination. The implementation of the Civil Service Program is in fact being undertaken to give primary school teachers in Sukamakmur district, Bogor Regency, the opportunity to develop this bulletin board media through training and mentoring activities, namely to create a bulletin board medium, theoretically feasible criteria. meet the right criteria in terms of format, content and appearance; have high applicability or are worth learning. The nonprofit activities of the Education Technology Study Program of the FIP UNJ are being evaluated to determine the extent to which educators' knowledge and skills in the design, development, use and evaluation of bulletin board media are increasing.